« Le monde dans une noix » - Markus Meumann (Mélanges de la Casa de Velázquez, 2014)
In 1697 there appeared in the bookshop of Johann Daniel Tauber in Nuremberg a large tome, richly illustrated with 48 folio copper plate engravings and titled Sculptura Historiarum Et Temporum Memoratrix. The book, which presents the principal events in universal history since the creation of the world in the form of a chronological summary, does not simply follow a strictly chronological order but is shaped on mnemotechnic principles. To help readers learn and remember historical facts, these are classified by millennia, by centuries and finally by decades. History is thus conceived as a list of the principal events in history. This virtual list is embodied first and foremost in sets of illustrations on 48 panel engravings each of which depicts a millennium—or a century as the case may be—which in turn are divided into ten panels; these last illustrate either a century (as a subdivision of a millennium) or a decade (as a subdivision of a century). The plates as such can thus be viewed as pictorial lists. This became fully apparent when in 1700, poorer-quality copies were made and published on their own, with no explanatory text, under the title Die Welt in einer Nuß («The world in a nutshell»).